Ontology of social interaction ethics from the source of surah Al Hujurat in the Quran / Mohamad Azlan Kamarulzaman - Kamarulzaman, Mohamad Azlan (Faculty of Computer and Mathematical Sciences, 2016)
With ontology, different concepts and terms can be collected and reunited on a single domain. In addition, knowledge can be easily delivered to users using ontology. At the same time, vast knowledge can be learnt from the Quran where different themes can be discussed including business, divine being, religious practices and many more. One particular topic that is quite interesting is social interaction ethics. Moreover, people in Malaysia also have shown a slight declining of social ethics among them especially teenagers nowadays. Hence, this project will develop ontology that can be used to organize or deliver the knowledge of social interaction ethics in the Quran to people. The ontology will be developed using the appropriate ontology development tools and method. Alongside this ontology will also be created, a semantic web which will present the information in the ontology so that it is easier for user to learn. From this project user can learn what are the encouraged and discouraged ethics as well as what are the verses that support these statements. Hopefully, user will be able to benefit from this project.